2017
DOI: 10.1073/pnas.1617922114
|View full text |Cite
|
Sign up to set email alerts
|

PIK3CA mutant tumors depend on oxoglutarate dehydrogenase

Abstract: Oncogenic PIK3CA mutations are found in a significant fraction of human cancers, but therapeutic inhibition of PI3K has only shown limited success in clinical trials. To understand how mutant PIK3CA contributes to cancer cell proliferation, we used genome scale lossof-function screening in a large number of genomically annotated cancer cell lines. As expected, we found that PIK3CA mutant cancer cells require PIK3CA but also require the expression of the TCA cycle enzyme 2-oxoglutarate dehydrogenase (OGDH). To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 63 publications
4
32
1
Order By: Relevance
“…Allen et al conducted a focused siRNA screen on TCA cycle enzymes, and found that many cancer cells highly depend on OGDH (the E1 component of KGDHC) for growth and survival (Allen et al, 2016 ). A recent study by Ilic et al demonstrated that cancer cells harboring oncogenic PI3K mutations require all three components of KGDHC, OGDH in particular, for proliferation (Ilic et al, 2017 ). These findings support the rationale to target KGDHC for cancer treatment.…”
Section: Potential Approaches To Target the Tca Cyclementioning
confidence: 99%
“…Allen et al conducted a focused siRNA screen on TCA cycle enzymes, and found that many cancer cells highly depend on OGDH (the E1 component of KGDHC) for growth and survival (Allen et al, 2016 ). A recent study by Ilic et al demonstrated that cancer cells harboring oncogenic PI3K mutations require all three components of KGDHC, OGDH in particular, for proliferation (Ilic et al, 2017 ). These findings support the rationale to target KGDHC for cancer treatment.…”
Section: Potential Approaches To Target the Tca Cyclementioning
confidence: 99%
“…It is well established that hyperactive PI3K/Akt signaling contributes to increased glycolytic rate, and recent studies have identified dependencies on specific metabolic enzymes that, when perturbed, impact glycolytic flux and consequently cancer cell viability ( 35 ). Notably, PIK3CA mutant cancer cell lines have elevated 2-oxoglutarate dehydrogenase (OGDH) activity, and inhibition of this enzyme leads to reduced tumor growth in vivo ( 35 ). The sensitivity to OGDH inhibition can be explained by the observed decrease in the NAD + /NADH ratio following accumulation of 2-oxoglutarate, thus limiting the available NAD + needed for glycolysis ( 35 ).…”
Section: Regulation Of Ros Production By Pi3k/akt Signalingmentioning
confidence: 99%
“…Notably, PIK3CA mutant cancer cell lines have elevated 2-oxoglutarate dehydrogenase (OGDH) activity, and inhibition of this enzyme leads to reduced tumor growth in vivo ( 35 ). The sensitivity to OGDH inhibition can be explained by the observed decrease in the NAD + /NADH ratio following accumulation of 2-oxoglutarate, thus limiting the available NAD + needed for glycolysis ( 35 ). Interestingly, OGDH is a potent source of ROS and this, together with the need to maintain a stable NAD + /NADH ratio, suggests that maintaining redox homeostasis is essential for the proliferation of PIK3CA mutant tumors ( 35 , 36 ).…”
Section: Regulation Of Ros Production By Pi3k/akt Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…This complex is strongly essential in five Her2+ cell lines but nonessential in 8 others, suggesting the presence of further metabolic subtypes within the recognized Her2+ subtype [26]. A recent report indicates that dependency on αKGDH is driven by PIK3CA mutations [27]. However, the differential sensitivity to perturbation in our network is not correlated with PIK3CA mutation status: 3/5 sensitive cell lines and 4/8 insensitive cell lines carry oncogenic PIK3CA mutations (P=0.59, Fisher's exact test).…”
Section: Clusters In the Coessentiality Network Are Defined By Distinmentioning
confidence: 97%